Differences in home food availability of high- and low-fat foods after a behavioral weight control program are regional not racial - West Delia; Harvey-Berino Jean; Krukowski Rebecca A (BMC, 2010)
Abstract Background Few studies, if any, have examined the impact of a weight control program on the home food environment in a diverse sample of adults. Understanding and changing the availability of certain foods in the home and food storage practices may be important for creating healthier home food environments and supporting effective weight management. Methods Overweight adults (n = 90; 27% African American) enrolled in a 6-month behavioral weight loss program in Vermont and Arkansas. Participants were weighed and completed measures of household food availability and food storage practices at baseline and post-treatment. We examined baseline differences and changes in high-fat food availability, low-fat food availability and the storage of foods in easily visible locations, overall and by race (African American or white participants) and region (Arkansas or Vermont). Results At post-treatment, the sample as a whole reported storing significantly fewer foods in visible locations around the house (-0.5 ± 2.3 foods), with no significant group differences. Both Arkansas African Americans (-1.8 ± 2.4 foods) and Arkansas white participants (-1.8 ± 2.6 foods) reported significantly greater reductions in the mean number of high-fat food items available in their homes post-treatment compared to Vermont white participants (-0.5 ± 1.3 foods), likely reflecting fewer high-fat foods reported in Vermont households at baseline. Arkansas African Americans lost significantly less weight (-3.6 ± 4.1 kg) than Vermont white participants (-8.3 ± 6.8 kg), while Arkansas white participants did not differ significantly from either group in weight loss (-6.2 ± 6.0 kg). However, home food environment changes were not associated with weight changes in this study. Conclusions Understanding the home food environment and how best to measure it may be useful for both obesity treatment and understanding patterns of obesity prevalence and health disparity.